Krykfeie dicistrovirus: A novel dicistrovirus in velvety free-tailed bats from Brazil - Fumagalli, Marcilio Jorge; Souza, William Marciel de; Araujo, Jansen de; Modha, Sejal; Queiroz, Luzia Helena [UNESP]; Durigon, Edison Luiz; Murcia, Pablo Ramiro; Moraes Figueiredo, Luiz Tadeu (Elsevier B.V., 2019)
The Dicistroviridae family comprises positive single-stranded RNA viruses that are classified into Picornavirales order. These viruses are identified in arthropod hosts, including some having devastating economic consequences. Here, we described and characterized a novel nearly complete dicistrovirus genome identified in liver samples of velvety free-tailed bats (Molossus molossus) collected in June 2010 in Aracatuba city, Sao Paulo State, Brazil. This novel virus presents a genome of 9262 nucleotides in length and a typical dicistrovirus genome organization. Based on our phylogenetic analysis and ICTV criteria, we propose this virus as a novel species into the Triatovirus genus. Attempts of viral propagation in Vero E6 and C6/36 cell lines were unsuccessful. The novel dicistrovirus was detected only in one out of nine liver bat samples, representing for the first time an internal organ detection from a representative of this virus family.
Keywords: Dicistroviridae; Triatovirus; Picornavirales; Picornavirus